Developing and Implementing a Quality Assurance Strategy for Electroconvulsive Therapy. Issue 1 (March 2019) - Hollingsworth, Jessa; Baliko, Beverly; McKinney, Selina; Rosenquist, Peter
Abstract : Background: The literature provides scant guidance in effective quality assurance strategies concerning the use of electroconvulsive therapy (ECT) for the treatment of psychiatric conditions. Numerous guidelines are published that provide guidance in the delivery of care; however, little has been done to determine how a program or facility might ensure compliance to best practice for safety, tolerability, and efficacy in performing ECT. Objective: The objective of this project was to create a quality assurance strategy specific to ECT. Determining standards for quality care and clarifying facility policy were key outcomes in establishing an effective quality assurance strategy. Methods: An audit tool was developed utilizing quality criteria derived from a systematic review of ECT practice guidelines, peer review, and facility policy. All ECT procedures occurring over a 2-month period of May to June 2017 were retrospectively audited and compared against target compliance rates set for the facility's ECT program. Facility policy was adapted to reflect quality standards, and audit findings were used to inform possible practice change initiatives, were used to create benchmarks for continuous quality monitoring, and were integrated into regular hospital quality meetings. Results: Clarification on standards of care and the use of clinical auditing in ECT was an effective starting point in the development of a quality assurance strategy. Audit findings were successfully integrated into the hospital's overall quality program, and recognition of practice compliance informed areas for future quality development and policy revision in this small community-based hospital in the southeastern United States. Conclusions: This project sets the foundation for a quality assurance strategy that can be used to help monitor procedural safety and guide future improvement efforts in delivering ECT. Although it is just the first step in creating meaningful quality improvement, setting clear standards and identifying areas of greatest clinical need were crucial beginning for this hospital's growing program.